Joint application of beneficial microorganisms consortium and FitoMas-E® increases the agricultural indicators of beans - Calero-Hurtado, Alexander [UNESP]; Pérez-Díaz, Yanery; Rodríguez-Lorenzo, Mileidy; Rodríguez-González, Venancio (Universidad de Ciencias Aplicadas Y Ambientales - UDCA, 2022)
The use beneficial of microorganisms jointly with vegetal biostimulants can be an efficient alternative to improve the productivityofbeans.Thepurposeofthisresearchwastodetermine the effect of individual and joined application of the biostimulants ME-50® and FitoMas-E® in the agroproductive increase of the bean in the late sowing season. The research was conducted at the collective farmer “Martires de Taguasco”, Sancti Spiritus, Cuba. An experiment was carried out under field conditions with the cultivar “Velazco Largo”. The treatments were distributed in random blocks, in a 2×2 factorial scheme, with five replications, two levels absence and presence of the ME-50® consortium and its combination with no application and application of FitoMas-E®. The biostimulants effects were observed in i) growth parameters: leaves per plant, leaf area and dry mass; ii) production parameters: number of pods per plant, grains per pod, the mass of 100 grains and yield. The results revealed that the joint application of both biostimulants was more efficient in increasing growth and productivity than the individual application and the non-application of biostimulants, due to the yield increase of 10 and 71 %, respectively. The findings of this study suggest that the join application between ME-50® and FitoMas-E® constitutes an efficient, economical and viable alternative to increase bean productivity in the late sowing season.
Aplicación conjunta del consorcio microorganismos benéficos y FitoMas-E® incrementan los indicadores agronómicos del frijol
Keywords: Bioproduct; Fabaceae; Foliar application; Inoculation; Phaseolus vulgaris L